Bahasa Indonesia BahDevelopment of Augmented Reality (AR) Based Minibook Media on Solar System Material for Grade VI Elementary Schoolasa Indonesia - Suryani, Safira; Atharina, Filia Prima; Azizah, Mira (JURNAL PENDIDIKAN DASAR NUSANTARA, 2024)
This research is motivated by the challenges in learning the Solar System at SD Negeri 2 Gedangalas. These learning students' difficulties in understanding science learning about the Solar System in class VI, the lack of use of technology-based learning media, limitations in learning media that can support learning, as well as the lack of application of active and innovative learning in science learning about the Solar System in class VI. Therefore, the aim of this research is to develop Minibook Learning Media Based on Augmented Reality (AR) as an effort to overcom the challenges of learning the Solar System at SD Negeri 2 Gedangalas. This research is included in the Research and Development (R&D) category. Validation is carried out by material experts and media experts. The subjects of this research were students at SD Negeri 2 Gedangalas, with a small-scale trial involving 16 students and a large-scale trial involving 30 students . Data collection used an instrument in the form of a questionnaire. Data analysis was carried out descriptively qualitatively and descriptively quantitatively in the form of percentages. The research results showed that the validation of material experts in all aspects was rated "Very Good" with an average score of 93,35%. Media experts also gave a rating of "Very Good" with an average score of 95,37%. Small group testing showed student ratings of “Very Good” with an average score of 87,75. Thus, it can be concluded that the results of this research have produced an Augmented Reality (AR)-based Minibook learning media product that is effectively used by elementary school students.